The Role of Mother’s Bargaining Power on Children's Education in Indonesia - Pravitasari, Dinny; Widyawati, Diah (Jurnal Ekonomi Pembangunan, 2024)
The high dropout rate and low school participation rate at higher levels of education indicate low opportunities for continuing education. It will have an impact on the quality of human capital. In this case, improving the quality of human capital through education could be initiated from children as the generation who will play a role in future development. Several studies have found that education is associated with the mother's bargaining power. However, previous studies used indirect proxies. This research aims to provide evidence regarding the relationship between maternal bargaining power and the continuity status of children's educational levels using a direct proxy measure of the mother’s bargaining power. This study uses the decision-making information from IFLS 2000-2014 as the mother's bargaining power. Using the probit method, the mother's bargaining power based on household decisions has not been proven to be related to the continuity status of children's educational levels. For specific decisions regarding children's education, the mother's bargaining power has a significant and positive relationship.